menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Find (f+g) (x) f (x) = 4x - 4 and g (x) = 2x^2 - 3x
asked
May 1, 2021
175k
views
4
votes
Find (f+g) (x) f (x) = 4x - 4 and g (x) = 2x^2 - 3x
Mathematics
college
John Zumbrum
asked
by
John Zumbrum
5.7k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
2
votes
Answer: (f+g)(x) = 2x^2 + x - 4
Step-by-step explanation:
f(x) = 4x - 4
g(x) = 2x^2 - 3x
Find (f+g)(x):
(f+g)(x)
= (4x - 4) + (2x^2 - 3x)
= 4x - 4 + 2x^2 - 3x
= 2x^2 + x - 4
Markus Winand
answered
May 3, 2021
by
Markus Winand
4.9k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
3
votes
(f+g)(x) = f(x) + g(x)
= 4x - 4 + 2
- 3x
= 2
+ x - 4
Jesse Petronio
answered
May 7, 2021
by
Jesse Petronio
5.2k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.8m
questions
7.5m
answers
Other Questions
Aliyah has $24 to spend on seven pencils. After buying them she had $10. How much did each pencil cost?
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Find the quotient of 3,078 ÷ 27. A) 104 B) 109 C) 114 D) 119
Can someone help me with 5??? ASAP?
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org